Implementing Right to Information : Lessons from Experience - Dokeniya, Anupama (World Bank, Washington, DC, 2014)
This implementing right to information lessons from experience has attempted to sketch out the key areas that are important to address during the implementation of Right-to-Information (RTI). In particular, it has highlighted both the imperative of setting up a number of institutions to build capacity and support for RTI in the public sector as well as the challenges in sustaining implementation institutions as political will erodes. It has highlighted the critical importance of the underlying political economy and governance environment, an area often ignored in devising reforms but that is key to whether RTI ultimately works effectively or has any impact. The number of countries with RTI laws-laws that establish citizens `right` to have access to public information or operationalize such a right found in the constitution has exploded. Most of the new adopters are countries in Eastern Europe, Asia, Latin America, and most recently, Africa and the Middle East-countries. The international momentum translated into law when domestic dynamics were favorable, when political elites perceived that it is to their advantage to support the law in order to win political points with domestic constituencies and establish their democratic credentials internationally. In several countries, the transition to democracy also provided an opportunity when pro-reform coalitions of ruling and opposition parties, civil society groups, and media obviated sources of opposition or resistance to the passage of an RTI law.